По теореме Виета:
![image](https://tex.z-dn.net/?f=%5Cleft+%5B%0A%5Cbegin%7Bgathered%7D+x%3D-8%5C%5Cx%3D3%3Cspan%3E%5Cend%7Bgathered%7D%5Cright.%5C%5C%3C%2Fspan%3E2%29+x%5E4%2B3x%5E2-4%3D0%5C%5C+t%3Dx%5E2%2C+t%5Cgeq0%5C%5C+t%5E2%2B3t-4%3D0%5C%5C+%5Cleft+%5B+%5Cbegin%7Bgathered%7D+t%3D-4+%5Cnotin+t%5Cgeq0%5C%5C+t%3D1+%5Cend%7Bgathered%7D%5Cright.%5C%5C+x%5E2%3D1%5C%5C+x%3D%5Cpm1%5C%5C+)
\end{gathered}\right.\\2) x^4+3x^2-4=0\\ t=x^2, t\geq0\\ t^2+3t-4=0\\ \left [ \begin{gathered} t=-4 \notin t\geq0\\ t=1 \end{gathered}\right.\\ x^2=1\\ x=\pm1\\ " alt="\left [
\begin{gathered} x=-8\\x=3
\end{gathered}\right.\\2) x^4+3x^2-4=0\\ t=x^2, t\geq0\\ t^2+3t-4=0\\ \left [ \begin{gathered} t=-4 \notin t\geq0\\ t=1 \end{gathered}\right.\\ x^2=1\\ x=\pm1\\ " align="absmiddle" class="latex-formula">
Ответ: В